Aspects regarding the research in the field of electric vehicles implementation in the context of the sustainable development of the European road transport system - Gheorghe Neamțu (THOT Publishing House, 2021)
The scientific paper presents a concrete research carried out by the authors in order to implement some concepts of a technical nature, so that those interested in this field can get acquainted about a certain way of exposing the problems regarding the actions taken by the European authorities, regarding the implementation of electric vehicles at the level of some EU states, in the context of the sustainable and durable development of the European road transport system. Below we present a technical and managerial study with engineering nuances, through which readers can look at and understand the concept of sustainable development of this sector in a global context, through which we will demonstrate the efficiency and effectiveness of the Project of the Electric Vehicle Network in Urban Europe - URBACT II, (EVUE) [11][12], a research project carried out at European Union level in the field of electromobility and the measures taken to reduce pollution in 9 European cities. The research was carried out in public private partnership (cPPP) and was funded by the European Investment Bank (EIB). The initiative was launched in 2009 as a constituent element of the challenge: "Intelligent, green and integrated transport" under Horizon 2020 programme [9] as a result of the global economic crisis of 2008 and was completed in 2012 through 113 collaborative research projects [3] [12]. The paper highlights the achievements and shortcomings of this initiative, and finally the conclusions and subsequent directions of research in the field approached are presented.